Breeding Strategies for Improvement of Global Traits in Thai Indigenous Chicken - Duangjinda, Monchai (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
Poultry industry in Thailand has become a large industry and important for the economy of thecountry.With the food safety regulations, only evaporative system or closed system are allowed forcommercial scale of poultry production.A sustainable poultry production has promoted utilization ofindigenous chicken. Thai indigenous chicken (TIC) is defined as a native species. There are severalstrategies to improve economic traits in chickens. The improving growth, egg production and climatechange adaptation traits is a success model in improving Thai indigenous chicken genetics via theconventional and molecular breeding (using candidate genes approach), also crossbreeding withcommercial breeds for large scale production.Â Key Words: Thai Indigenous Chicken, Candidate Genes Approach, Exotic Breeds